The Powers of Evaluation: The Understanding and Practice of Evaluation in youth Ministry Communities of Practice in Illinois - Severe, Michael K. (Christian education journal, 2013)
Evaluation is a powerful tool for improvement yet is often perceived as simply a rearview mirror into the past. A two-tier qualitative method was used to uncover the practice and understanding of evaluation among youth pastors in Illinois. Reliance on indicators, such as stories and observation, tended to reinforce assumptions in practice. Evaluation was pervasive, powerfully guided perception, and primarily implicit.